The Effectiveness of Communicative Language Teaching Strategies in Improving Arabic Language Proficiency among Students at LIPIA Medan - Yudho Pratama; Hasrian Rudi Setiawan (Integrasi: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to analyze the effectiveness of communicative language teaching strategies in improving Arabic language proficiency among students at LIPIA Medan. The research employs a quantitative approach with a quasi-experimental design. The participants consist of students divided into an experimental group and a control group. Data were collected through pre-test and post-test assessments of Arabic language proficiency. The findings indicate a significant improvement in the Arabic language skills of students taught using communicative teaching strategies compared to those taught using conventional methods. This strategy is proven effective in enhancing students’ speaking, listening, reading, and writing skills. Furthermore, communicative teaching strategies also increase students’ motivation and active participation in the learning process. Therefore, this approach is recommended as an effective method for teaching Arabic at the higher education level.